FROM WORK TO TEXT AND BACK AGAIN - Tevdoradze, Nino (Online Journal of Humanities ETAGTSU, 2020)
It has become a common practice in contemporary literary criticism that the concepts “literary text” and “literary work” are used as interchangeable synonyms and over the past few decades, the term "text" has occupied the place of "work". This article aims to discuss the reasons for stimulating this tendency and to specify the appropriateness of such use. It also stresses the particular relevance of not conflating the two aforementioned concepts into the same area of enquiry and attempts to draw the line between them. Full Text (PDF)